Epoxyalkanoyls as novel ACE inhibitors - Choo, HYP; Yoon, HR; Park, HS; Kim, DH; Park, J; Kim, J (PHARMACEUTICAL SOCIETY KOREA, 1998)
The epoxyalkanoyl derivatives were designed and synthesized as ACE inhibitors. Coupling of unsaturated carboxylic acids with amino acids and following epoxidation with dimethyldioxirane gave the epoxyalkanoyls with high yield. The inhibitory activity of synthesized compounds on angiotensin converting enzyme was IC50 values of 0.06 similar to 5.5 mu M.
Keywords: ANGIOTENSIN-CONVERTING ENZYME; ANTIHYPERTENSIVE AGENTS; DESIGN; ACIDS